Newspaper Framing of the Nigerian Armed Forces Operation Python Dance Ii in South-East Nigeria (Global Journal of Human-Social Science, 2020)
This study is an analysis of how the Nigerian newspapers framed the Nigerian Armed Forces' "Operation Python Dance II" with a view to identifying the dominant frames in the stories published. The theoretical underpinning for the study is the Frame analysis theory propounded by Erving Goffman. The content analysis method was used to generate quantitative data for analysis from the four selected newspapers, the analysis of the newspapers generated a total of 62 stories in 47 editions from the 124 editions sampled and used to address the research questions. Findings from the study revealed that the human interest frame was the dominant frame of reportage with 35% of total reports while the security and attribution of responsibility frames had a considerable amount of stories with 23% and 18% respectively. Further findings from the analysis revealed that the stories on OPD II were interpretative as majority (71%) of the stories were reported using the interpretative genres of editorials, feature stories, columns/opinions and interviews. From the findings, it is recommended the media and the military should in subsequent exercises like this to prepare the members of the society for an upcoming exercise by carrying public service announcements on the issue while the military should organize press conferences on issues like this to avoid misconceptions and create awareness.